Elasticity and magnetism of Ni2 MnGa premartensitic tweed. Issue 10 (22nd April 2014) - Seiner, Hanuš; Kopecký, Vít; Landa, Michal; Heczko, Oleg
<x xml:space="preserve">Abstract</x> Magnetic, magneto‐elastic and elastic measurements were used to characterize the thermal evolution of the premartensite phase of Ni2 MnGa. The premartensitic transition is shown to correspond to a sharp maximum of magnetostriction and a pronounced minimum of the (110) <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fdds79m" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />〈11‾0〉</alternatives> shear stiffness (the <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fdds76z" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />c′</alternatives> elastic coefficient); no additional softening of the <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fdds6x1" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />c′</alternatives> coefficient prior to the martensitic transformation was observed. In contrast, a significant softening of the (100) <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fdds6vx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />〈010〉</alternatives> stiffness (the <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fdds72r" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />c44</alternatives> elastic coefficient) was observed in the vicinity of the martensitic transition, while this coefficient is fully unaffected by the premartensitic transition. A simple two‐dimensional model of the tweed is presented to explain this mutual independence between the <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fdds716" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />c′</alternatives> and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fdds6st" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />c44</alternatives> shears and the effect of tweed formation on both of them.